Baby Boomers and the Long-Term Transformation of Retirement and Volunteering: Evidence for a Policy Paradigm Shift. (October 2018) - Chambré, Susan M.; Netting, F. Ellen
In this article, we analyze two predictions about baby boomers that have contributed to the current policy paradigm: that the boomers will reinvent retirement, and that they have the potential to engage in higher levels of formal volunteering than previous generations. Empirical evidence from various studies and surveys do not support this paradigm. In fact, the data lead to the conclusion that baby boomers are neither initiating the reinvention of retirement, nor are they the initiators of a surge in volunteerism. Instead, they are part of an ongoing evolution of retirement and volunteerism begun by their parents' generation. We propose several assumptions to construct an alternative policy paradigm: Baby boomers need to be recognized as a diverse age cohort whose engagement is multi-faceted. Volunteer recruitment and oversight require creative approaches which focus on the communal and membership aspects of volunteering rather than focusing on volunteering as unpaid "work."